How Do African Farm Households Respond to Changes in Current and Past Weather Patterns? A Structural Panel Data Analysis from Malawi. (17th November 2017) - Sesmero, Juan; Ricker-Gilbert, Jacob; Cook, Aaron
Abstract : We use three waves of nationally representative household-level panel data from Malawi to estimate a structural model characterizing the response of smallholder farm households to current and past weather patterns, and the subsequent impacts on household net income. We also quantify heterogeneity among households along the wealth spectrum regarding their ability to adapt to evolving weather patterns. This approach yields two key findings. First, adverse weather history prompts households to devote more time to maize cultivation on their own farms, to the detriment of other, possibly more remunerative income sources. Households also reduce application of productivity-enhancing inputs, such as fertilizer and improved maize varieties, in response to adverse weather history. Our results are robust to different clustering structures and falsification tests aimed at ruling out alternative explanations to observed trends. Second, we find that, by maintaining a more diversified income structure, wealthier households are better able to adapt to adverse weather history. Consequently, adverse changes in past weather may be regressive in nature, creating a "climate-induced" poverty trap that locks poor smallholder households into low-value maize cultivation from season to season. This finding suggests that developing more weather-resilient maize varieties and promoting smallholder livelihood diversification strategies may help mitigate the effects of adverse weather on the most vulnerable households.